DEVELOPMENT OF E-MODULES FOR MAKING DATA FLOW DIAGRAMS IN INFORMATION SYSTEMS ANALYSIS AND DESIGN COURSES AT INSTIKI INDONESIA CAMPUS - Aniek Suryanti Kusuma; Desak Made Dwi Utami Putra; Ayu Gede Willdahlia; Ni Kadek Nita Noviani Pande; Welda Welda (Sean Institute, 2023)
The learning process at theInstitute of Business and Technology Indonesia (INSTIKI) uses teaching materials in the form of slides, teaching materials and modules. All teaching materials used are PDF files which are copies of printed materials. Information cannot flow directly into the presentation of teaching materials and learning objectives cannot be achieved. The purpose of this research is to develop a Data Flow Diagram Design E-module to support the Information Systems Analysis and Design course. The method used in this research is the research and development (R&D) method, which uses the stages of the ADDIE access model. This research was conducted in several stages, namely in the first stage, student needs analysis and curriculum analysis were carried out. The second step is design which defines the elements needed. The third phase is the product implementation phase according to the design. The fourth step is to implement the e-module using Flip Bookmaker. In the fifth phase, the implementation results are evaluated through group tests and the effectiveness of the product is verified. This E-module product will be tested by testing the level of student understanding, material test and media expert test.